Deletion of the GABA(A) Receptor α1 Subunit Increases Tonic GABA(A) Receptor Current: A Role for GABA Uptake Transporters - Ortinski, Pavel I. (J Neurosci, 2006)
The loss of more than half the number of GABA(A) receptors yet lack of pronounced phenotype in mice lacking the gene for the GABA(A) α1 subunit is somewhat paradoxical. We explored the role of tonic GABA(A) receptor-mediated current as a target of compensatory regulation in the α1 knock-out (−/−) mice. A 62% increase of tonic current was observed in the cerebellar granule cells (CGCs) of α1(−/−) compared with wild-type (+/+) mice along with a 67% increase of baseline current variance. Examination of whole-cell currents evoked by low concentrations of GABA and 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol suggested no upregulation of α6 and δ subunit-containing GABA(A) receptors in the α1(−/−), confirming previous biochemical studies. Single-channel current openings were on average 32% shorter in the α1(−/−) neurons. Single-channel conductance and frequency of opening were not different between genotypes. Tonic current induced by application of the GABA transporter GAT-1 blocker NO711 (1-[2([(diphenylmethylene)imino]oxy)ethyl]-1,2,5,6-tetrahydro-3-pyridinecarboxylic acid hydrochloride) was significantly larger in the α1(−/−), suggesting an increase of ambient GABA concentration. Experiments done with a known concentration of extracellular GABA complemented by a series of biochemical experiments revealed a reduction of GAT activity in α1(−/−) without an identifiable reduction of GAT-1 or GAT-3 protein. We report increased tonic GABA(A) receptor-mediated current in the α1(−/−) CGCs as a novel compensatory mechanism. Our data establish a role for GABA transporters as regulators of neuronal excitability in this and relevant models and examine other tonic conductance-regulating mechanisms responsible for the adaptive response of the cerebellar network to a deletion of a major synaptic GABA(A) receptor subunit.